Simulation Of Transmission Matching To Improve Cng-Di Vehicle Performance - Adlan, Hamzah (2007)
This research presents the process of designing a simulation tool to predict dynamic performance of a vehicle. In this case, PROTON WAJA powered by newly developed CNG-DI CamPro prototype engine was taken as model to be predicted and at the same time to improve vehicle performance. Besides that, the potentials of Natural Gas and Direct Injection technology were reviewed as one of the main elements in this project. However this paper will not cover the design change or modification required to optimize Natural Gas as a fuel. Performance of the CNG-DI engine was simulated to match with the five speed manual transmission. In order to calculate the vehicle performance, combination of gear ratio and final drive selection was carried out. Three gear ratios and final drives combination were selected and compared. The best gear ratio combined with best final drive will decide the best performance. Besides that, comparison between simulation result and actual test conducted by vehicle manufacturer at the same test basis was also done to verify the accuracy of simulation tool. The tool was design to ease engineers or researchers when comes to transmission selection for a given vehicle.